Penerapan Keselamatan dan Kesehatan Kerja pada Pegawai di Rumah Sakit - Maulidya Permata (Jurnal Anestesi, 2024)
With increasing activity and the development of new methods and increasingly sophisticated equipment in hospitals, the problems of Occupational Health and Safety in hospitals (K3-RS) are becoming increasingly complex. Potential dangers in hospitals, apart from infectious diseases, there are also potential other dangers that affect the situation and conditions in hospitals, namely work accidents, explosions, fires, accidents related to electrical installations, and other sources of injury, radiation, dangerous chemicals, anesthetic gases, psychosocial and ergonomic disorders. All the potential dangers mentioned above clearly threaten the life and life of employees, patients and visitors in the hospital environment. Therefore, the implementation of K3 in hospitals absolutely must be implemented.